Timur Kuran’s Critique of Zakat and Waqf and Their Relevance in the Modern Economy - Afif Saeful Ulum; Jamal Abdul Aziz (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This article discusses Timur Kuran's critique of zakat and waqf in Islamic economics and its relevance in the context of modern economics. Kuran argues that although these two instruments have noble social goals, their implementation is less effective in supporting sustainable economic growth. Zakat tends to be used for short-term consumption and is less flexible in adapting to the dynamics of the modern economy, making it less able to become the main instrument in poverty alleviation. Meanwhile, waqf is considered a static asset with rigid management, which often hinders its optimal use in economic development. Through a descriptive-analytical approach, this study explores Kuran's arguments by comparing them to the current concepts and practices of zakat and waqf. The results show that although Kuran's critique has a strong basis, reforms in the zakat and waqf systems, such as professionalization of management and implementation of productive investment schemes, can increase their effectiveness in supporting social welfare and economic growth. Therefore, adaptation and innovation in the management of zakat and waqf are needed to remain relevant as Islamic economic instruments in the modern era.